Transnational industrial relations in Europe - Reiner Hoffmann; Otto Jacobi; Berndt Keller; Manfred Weiss (Hans-Böckler-Stiftung, 2000)
This is the third volume dedicated to a World Congress of the IIRA: the one for the Tokyo Congress in 2000 and it is dealing with the European scene. The perspective reflects the fact that Europe has reached a stage where it does no longer make too much sense to analyse national systems in isolation: they have to be put into the European context. The development of structural elements for a European industrial relations pattern has become an even more urgent task in view of the introduction of the European monetary union. Whether and how far collective bargaining can be coordinated throughout Europe or whether the trade unions are already in a stage to be a relevant actor on European level, are burning questions to be asked. The impact of already existing patterns of workers' participation on the spirit of European industrial relations has to be reflected. The still dramatic unemployment situation has led to a joint job creation strategy on EU level whose functioning needs careful analysis. In view of the forthcoming enlargement of the EU it has in addition become of utmost importance to reflect on the question how the industrial relations systems of the newcomers can be integrated in the already existing pattern. These and other aspects of the generation of a European industrial relations machinery are dealt with in this volume.
Keywords: 330; Arbeitsbeziehungen; Tarifverhandlungen; Internationale Arbeitsbeziehungen; EU-Sozialpolitik; Betriebsrat; EU-Staaten